Catalytic cracking of crude palm oil using Cr/palm shell charcoal impregnation catalyst - Suryadri, Hadistya; Juanda, Adrisma; Nazarudin, Nazarudin (Konversi, 2023)
The study of synthesizing Cr/activated palm shell charcoal catalyst by impregnation method has been done. Cr/Activated Charcoal was made using variation of chromium concentration (1%, 2% and 3%). Change in diffraction pattern in XRD analysis for charcoal before modification and after modification showed chromium has been successfully impregnated to the catalyst. The higher the chromium compound concentration used, the greater %-weight of chromium in the catalyst. It was found that the use of Cr-2%/Charcoal catalyst was able to increase the percentage of cracking liquid yield at the temperature of 550oC  as much as 62,44% compared to the percentage of liquid yield from thermal cracking was 60,1% at the same temperature. It was also observed, using the Cr/Charcoal catalyst from impregnation method is more effective than catalyst from ion exchange method. However, the density of the cracking liquid yield is not yet close to the standard density range for fuel.